2004
DOI: 10.1160/th04-02-0087
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of central venous line-related thrombosis by continuous infusion of low-dose unfractionated heparin, in patients with haemato-oncological disease

Abstract: We have conducted a prospective randomized controlled trial to evaluate the role of low-dose unfractionated heparin prophylaxis in preventing central venous line-related thrombosis in patients with haemato-oncological disease. Patients were randomly assigned to receive either prophylactic intravenous unfractionated heparin (continuous infusion of 100 IU/kg/daily) or 50 ml/daily of normal saline solution as a continuous infusion. CVLs were externalized, non tunneled, double lumen catheters. All CVLs were placed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(11 citation statements)
references
References 42 publications
(47 reference statements)
0
11
0
Order By: Relevance
“…[23][24] Recently, in a randomised controlled trial, we showed that low-dose of UFH was safe and effective to prevent CVC-related thrombosis in patients with haemato-oncological disease. 25 However, many clinicians are reluctant to prescribe anticoagulant prophylaxis routinely in patients with cancer and a CVC because of the low expected incidence of thrombosis and the fear of bleeding during anticoagulant prophylaxis. [26][27] In conclusion, our results suggest that inherited prothrombotic abnormalities contribute substantially to CVC-related thrombosis in HSCT recipients.…”
Section: Discussionmentioning
confidence: 99%
“…[23][24] Recently, in a randomised controlled trial, we showed that low-dose of UFH was safe and effective to prevent CVC-related thrombosis in patients with haemato-oncological disease. 25 However, many clinicians are reluctant to prescribe anticoagulant prophylaxis routinely in patients with cancer and a CVC because of the low expected incidence of thrombosis and the fear of bleeding during anticoagulant prophylaxis. [26][27] In conclusion, our results suggest that inherited prothrombotic abnormalities contribute substantially to CVC-related thrombosis in HSCT recipients.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of CRT varies considerably among studies, and has dramatically decreased over time. Earlier studies published in the 1980s and 1990s reported rates as high as 66%, but more recent trials have shown that only 14-18% of patients with cancer and a central venous catheter have evidence of CRT when screening venography or ultrasonography is performed [6,[10][11][12]. Symptomatic CRT occurs much less frequently, at a rate of 5% or lower in prospective cohort studies [13][14][15].…”
Section: Incidence Of Crtmentioning
confidence: 99%
“…The efficacy and safety of using anticoagulant prophylaxis to prevent CRT have been investigated in a number of randomized trials (Table 3) [10][11][12][38][39][40][41][42][43][44][45]. The earliest studies suggested that low-dose warfarin (1 mg daily) or LMWH at a standard postoperative prophylaxis dose could significantly reduce the incidence of CRT in cancer patients [38,43].…”
Section: Prevention Of Crtmentioning
confidence: 99%
See 1 more Smart Citation
“…In another perspective, only one study showed that the continuous low-dose infusion of heparin (100 U/kg per day) reduces the incidence of PICC-associated thrombosis to 1.5%. This finding is attributed to the higher incidence of chemotherapy-induced thrombocytopenia [13]. Many risk factors for PICC-related thrombosis were analyzed in several studies such as obesity, gender, history of DVTs and use of anticoagulation but none were conclusive and only revealed conflicting results [14][15][16][17].…”
Section: Discussionmentioning
confidence: 99%